ANALISIS TINGKAT KEPUASAN KONSUMEN TERHADAP KUALITAS PELAYANAN PADA TOKO BUKU ANGGREK PALEMBANG - Dibyantoro Dibyantoro; Heri Setiawan; Nashirah Tamimi (Orasi Bisnis : Jurnal Ilmiah Administrasi Niaga, 2014)
This reseach done in Anggrek book store and aimed to know how big the level of customer satisfaction, to know priority necessary repairs in order understand deficiencies of service quality and determining the dimension that the most dominant in customer satisfaction. It is based on 5 dimension of service quality there are tangibles, reliability, responsiveness, assurance and empathy.research conducted on 100 respondents into Anggrek book store. The result of the study are average customers feel quite satisfied with the quality of service provided by Anggrek book store. There are 8 items that should be fixed and the dimensions most give satisfaction to customers is assurance with the degree of satisfaction 93,5%. Based on the research result then expected management to improve the quality service is not good in the eyes of customer, consider priority correction and maintain the quality of service that has been good.